First up, thank you to Dr. Stitz, Dr. Zeager and all other contributors/staff for a wonderful free book.
On page 642 (or 654 depending on which page number format is chosen):
For Example 8.7.2
PART 3, CASE 2
z = 1 is substituted into EQUATIONS 1 and 3.
E1 leads to a contradiction.
E3 is claimed to give y = 0, but is this claim correct?
E3 doesn't involve z, so shouldn't we still have (x-2)^2 + y^2 = 1 instead of
(1-2)^2 + y^2 = 1 as mentioned in the text?
Am I missing something or is there a mistake in the text?